2013
DOI: 10.5301/ejo.5000396
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Finding Study of Preoperative Intravenous Dexmedetomidine in Children's Emergence Delirium after Epiblepharon Surgery

Abstract: Dexmedetomidine can be safely used between 1.0 and 1.43 µg/kg to attenuate children's ED after sevoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Indeed, recent reports have shown that dexmedetomidine exerted both preconditioning and postconditioning effects against ischemic injury in hippocampal organotypic slice cultures (Dahmani et al, 2010), and downregulated apoptosis-promoting protein (Engelhard et al, 2003). A large body of experimental models and clinical setting support dexmedetomidine's neuroprotective properties, including attenuating delirium, preserving sleep architecture, preserving ventilatory drive and decreasing sympathetic tone and inflammatory response (Yang and Lee, 2014;Bekker et al, 2013;Zhang et al, 2014aZhang et al, , 2014b. Our findings in POCD add dexmedetomidine a new neuroprotective property.…”
Section: Sp3+d15mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent reports have shown that dexmedetomidine exerted both preconditioning and postconditioning effects against ischemic injury in hippocampal organotypic slice cultures (Dahmani et al, 2010), and downregulated apoptosis-promoting protein (Engelhard et al, 2003). A large body of experimental models and clinical setting support dexmedetomidine's neuroprotective properties, including attenuating delirium, preserving sleep architecture, preserving ventilatory drive and decreasing sympathetic tone and inflammatory response (Yang and Lee, 2014;Bekker et al, 2013;Zhang et al, 2014aZhang et al, , 2014b. Our findings in POCD add dexmedetomidine a new neuroprotective property.…”
Section: Sp3+d15mentioning
confidence: 99%
“…Dexmedetomidine improved neuronal apoptosis caused by isoflurane in newborn mice (Sanders et al, 2009) and increased the expression of anti-apoptosis protein while reduced the expression of apoptosis-promoting protein in intracerebral hemorrhage rats (Hwang et al, 2013). Experimental and clinical practice have revealed that dexmedetomidine is neuroprotective on delirium, stress and inflammatory response (Yang and Lee, 2014;Bekker et al, 2013;Zhang et al, 2014aZhang et al, , 2014b. Dexmedetomidine treatment converted disordered electroencephalogram waves to normal non-rapid eye movement wave in patients with sleep disorder, an important induction factor of POCD (Huupponen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Pickard et al [32], that included 12 randomised trials, concluded that both dexmedetomidine and clonidine reduced the incidence of emergence delirium, although recovery times were prolonged. One study [33] demonstrated that pre-operative infusion of dexmedetomidine reduced the incidence following eye surgery, although as this may be an impractical way to administer the drug whilst the patient is awake, intranasal administration is probably an acceptable alternative [34]. An intra-operative intravenous infusion of dexmedetomidine at 0.2-1.0 lg.kg…”
mentioning
confidence: 99%
“…In 2008, Enlow and Ardizzone published a review of four randomized controlled trials and found that perioperative administration of dexmedetomidine significantly reduced the incidence of ED in children without increasing the risk of side effects [57,58,[67][68][69]. Similar results were seen in a more recent study which found dosages of dexmedetomidine between 1.0 and 1.43 µg/kg safely attenuating ED in 25 pediatric patients after sevoflurane anesthesia [70].…”
Section: Dexmedetomidinementioning
confidence: 72%